The Effectiveness of using mass media in teaching English language for EFL students - BELAOUEDJ, Houda (My University, 2018)
This paper aims to identify the effectiveness of mass media in learning English as a foreign language among Algerian students. Midle school year students first year, second year and third year at Belaouedj Aid Secondary School were identified as the participants of this study. The instrument of this study is a two questionnaire, which is constructed in order to explore the students’ and teachers’ perceptions and attitudes on using mass media for English language learning and teaching. It is found that majority of the participants use mass media to enhance their learning and teaching. Moreover, the result revealed that learning embedded with mass media may help improve learning activities which in turn leads to the success of learning English as a foreign language. Apart from that, some of the problems encountered when using mass media and combined group work in the learning and teaching of English as a second language at Tertiary level are also highlighted. Most importantly, the students agreed that social media has by and large affected in their English language learning skills. Mass media can also benefit students with different learning style. It is also likely that student positive perception of media in teaching has effects on language learning since motivation and attitudes.Apart from that, the result also suggests that teachers generally are positive to use media in education and believe that students can learn more through mass media. Most importantly, the students agreed that mass media has by and large affected in their English language learning skills.
First-second third student’s Case study at BELAOUEDJ Laid secondary school Relizane
Keywords: Language teaching; Mass Medi; Learning English as Foreign Language